Trypsin-Immobilized Metal-Organic Framework as a Biocatalyst In Proteomics Analysis - Shih, Yung-Han; Lo, Sheng-Han; Yang, Ni-Shin; Singco, Brenda; Cheng, Yi-Jie; Wu, Cheng-You; Chang, I-Hsin; Huang, Hsi-Ya; Lin, Chia-Her (ChemPlusChem (Weinheim, Germany), 2012)
Enzyme immobilization: The protease enzyme was successfully immobilized onto dicyclohexylcarbodiimide (DCC)‐activated metal–organic frameworks (MOFs). After separation by nano‐LC‐MS2 (liquid chromatography–mass spectrometry), detection, and database searching the protein digestion efficiency of trypsin‐MOF was comparable to traditional in‐solution digestion (see figure). Furthermore, the trypsin‐MOF was reusable.